ANTIBACTERIAL EFFECTIVENESS TEST OF ETHANOL EXTRACTS OF PARE FRUIT (MOMORDICA CHARAN) AGAINST STREPTOCOCCUS MUTANS, THE CAUSE OF DENTAL CARIES IN THE PHARMACEUTICAL LAB OF EFARINA UNIVERSITY PEMATANG SIANTAR - Mustaruddin; Beta Hanindiya (PT. Radja Intercontinental Publishing, 2022)
Bitter gourd (Momordica charantia L) is a plant that contains quite a lot of compounds such as alkaloids, flavonoids and saponins in its fruit. Based on this, bitter melon has considerable potential to be used as an antibacterial for Streptococcus mutans. The bacterium Streptococcus mutans belongs to a group of round-shaped Gram-positive bacteria that cause dental caries. This study aims to determine the antibacterial effectiveness of several concentrations of ethanol extract of bitter gourd against Streptococcus mutans bacteria. Antibacterial testing of the ethanol extract of bitter gourd was carried out by measuring the Diameter of Inhibitory Area (DDH) through the paper disc diffusion method and the Minimum Inhibitory Concentration (MIC) through the agar dilution method. DDH testing was carried out on bitter melon extract concentrations of 70%, 60%, 50%, 40%, 30% and amoxicillin 30 pg/mL as positive control and distilled water as negative control. While MIC testing was carried out at concentrations of 30%, 35%, 40%, 45%, 50%, 55% and 60%. The results showed that the ethanol extract of bitter melon was less effective as an antibacterial against Streptococcus mutans, because the inhibition zone formed on the DDH test was not absolute or did not form a perfect circle. However, in MIC it can be seen that at a concentration of 50% the ethanol extract of bitter gourd fruit can inhibit it slightly and at a concentration of 60% it is seen that there is no bacterial growth, so it can be concluded that MIC is at a concentration of 60%. The results showed that the ethanol extract of bitter melon was less effective as an antibacterial against Streptococcus mutans, because the inhibition zone formed on the DDH test was not absolute or did not form a perfect circle. However, in MIC it can be seen that at a concentration of 50% the ethanol extract of bitter gourd fruit can inhibit it slightly and at a concentration of 60% it is seen that there is no bacterial growth, so it can be concluded that MIC is at a concentration of 60%. The results showed that the ethanol extract of bitter melon was less effective as an antibacterial against Streptococcus mutans, because the inhibition zone formed on the DDH test was not absolute or did not form a perfect circle. However, in MIC it can be seen that at a concentration of 50% the ethanol extract of bitter gourd fruit can inhibit it slightly and at a concentration of 60% it is seen that there is no bacterial growth, so it can be concluded that MIC is at a concentration of 60%.